2013
DOI: 10.1016/j.neurobiolaging.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-6 activity predicts lower episodic memory ability in aged individuals

Abstract: Caspase-6 (Casp6), a cysteinyl protease that induces axonal degeneration, is activated early in Alzheimer Disease (AD) brains. To determine whether Casp6 activation is responsible for early cognitive impairment, we investigated the abundance of Casp6 activity, paired helical filament–1 (PHF-1) phosphorylated Tau and amyloid beta peptide (Aβ) pathology by immunohistochemistry in the hippocampal formation of aged non–cognitively impaired (NCI) individuals. Casp6 activity was restricted to the entorhinal cortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 36 publications
7
43
1
Order By: Relevance
“…Previously, a semiquantitative assessment correlated the amount of Casp6 activity in ERC and CA1 with lower performance in declarative memory. 6 The Casp6 activity measured with neoepitope anti-active Casp6 immunostaining correlated significantly with neoepitope TauDCasp6 immunostaining, and each immunostaining correlated similarly with a lower performance in cognitive abilities in the CA1 region of the hippocampus. Herein, a more in-depth quantitative analysis of the amount of TauDCasp6/mm 2 in the CA1 of 16 aged NCI cases (demographics and cognitive scores are in Table 1) showed that the level of Casp6 activity assessed with TauDCasp6 immunohistological staining correlated negatively with global cognitive scores (Spearman rank r ¼ À 0.615, P ¼ 0.011) and declarative EP (r ¼ À 0.639; P ¼ 0.008) and semantic memories (SEs: r ¼ À 0.562, P ¼ 0.023) (Figure 1d).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Previously, a semiquantitative assessment correlated the amount of Casp6 activity in ERC and CA1 with lower performance in declarative memory. 6 The Casp6 activity measured with neoepitope anti-active Casp6 immunostaining correlated significantly with neoepitope TauDCasp6 immunostaining, and each immunostaining correlated similarly with a lower performance in cognitive abilities in the CA1 region of the hippocampus. Herein, a more in-depth quantitative analysis of the amount of TauDCasp6/mm 2 in the CA1 of 16 aged NCI cases (demographics and cognitive scores are in Table 1) showed that the level of Casp6 activity assessed with TauDCasp6 immunohistological staining correlated negatively with global cognitive scores (Spearman rank r ¼ À 0.615, P ¼ 0.011) and declarative EP (r ¼ À 0.639; P ¼ 0.008) and semantic memories (SEs: r ¼ À 0.562, P ¼ 0.023) (Figure 1d).…”
Section: Resultsmentioning
confidence: 85%
“…This could explain why removal of Ab in individuals with mild AD did not delay progression of the disease. 41 Although there is still considerable support for amyloid being a cause of AD, 42 there is also evidence to indicate that Casp6 can be upstream or parallel to Ab and NFT production: lack of correlation between Ab and memory performance despite a strong correlation with Casp6 and PHF-1 in aged hippocampi, 6 Casp6-dependent Ab production in human CNS primary neuron cultures, 15,16 Casp6-dependent, but Ab-independent, neuritic degeneration in APP-transfected human primary neurons, 14 and caspase activity leading to NFT in mice. 8 Targeting Casp6, in addition to Ab and NFT, may be required to efficiently prevent AD progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, experiments in hippocampal primary cultures demonstrate that STK4, an homolog of STK3, is phosphorylated upon oxidative stress by c-abl leading to the stabilization of the protein expression of STK4 and the STK4-FOXO mediated cell death (Xiao et al 2011). Moreover, CASP6 is activated in neurodegenerative diseases and its activity in the hippocampal CA1 region is sufficient to induce neuronal degeneration, inflammation and age-related memory impairment (LeBlanc et al 2014;Ramcharitar et al 2013;Graham, Ehrnhoefer, and Hayden 2011b;Wang et al 2015). Thus, the increase in mRNA expression of STK3 and CASP6, a protease that cleaves STK3, highlight a possible role for STK3 in the neurodegeneration process in AD and potentially other neurodegenerative diseases.…”
Section: Caspases Expression and Processing Of Stk3 In The Brainmentioning
confidence: 99%
“…Activation of caspases is observed in many physiological and pathological processes including Alzheimer disease, Huntington disease, stroke and aging (Broughton, Reutens, and Sobey 2009;Graham, Ehrnhoefer, and Hayden 2011a;LeBlanc 2013;Lee and Kim 2006;Pattison et al 2006;Snigdha et al 2012). The expression levels and activity of caspases during the aging process is organ and tissue specific.…”
Section: Introductionmentioning
confidence: 99%